Pengaruh Kepemilikan Media terhadap Agenda Setting di Indonesia - Retno Dewanti; Dwi Putri , Hemiliana; Lusianwati, Hayu (DIVERSITY: Journal of Multi Science Linearity, 2025)
This study analyzes the influence of media ownership and organizational structure on determining news content in Indonesia, using the 2024 Election as a case study using Shoemaker & Reese's Hierarchy of Influences framework at the Organizational Influences on Content level. The purpose of this research is to understand the extent to which organizational structural interests shape public perception through editorial policies. The method used is a qualitative case study with content analysis of news coverage during the campaign period. The results show that media ownership, concentrated in conglomerates with specific political affiliations, significantly determines the agenda, framing, and intensity of coverage. Editorial routines such as reliance on official sources, standard formats, and deadline pressures serve as instruments for implementing editorial policy. Three main patterns were identified: positive coverage of candidates aligned with the owners, the omission of sensitive issues, and imitation of the agendas of major media outlets by smaller media outlets, which has resulted in reduced diversity of issues in the public sphere. In conclusion, news content reflects political realities "curated" by structural interests and market logic rather than actual facts on the ground. Therefore, strengthening media independence, diversity of perspectives, and public media literacy are necessary to maintain the media's function as a pillar of democracy.